Governance and Participation in Policy Literature on Synthetic Biology - Siewert, Stephanie; Kieslich, Katharina; Braun, Matthias; Dabrock, Peter (Springer Science and Business Media B.V., 2023)
The chapter deals with the different positions in engaging the public(s) in the field of synthetic biology and provides an overview of the most prominent avenues in research, policy, and non-governmental action. Against the notion that participation is merely “management of perceptions” or “informing the public”, the authors argue for a holistic perspective in participatory approaches that perceives of informative and deliberative participation as equally valid degrees of activation. Furthermore, the authors question an overall emphasis on either institutional or individual responsibilities in the dialogue with the public.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Literature Review; Participatory Approaches; Public Engagement; Stakeholders